Reply to the 'Comment on "Structural, electrical and multiferroic characteristics of lead-free multiferroic: Bi(Co0.5Ti0.5)O3–BiFeO3 solid solution"' by P. E. Tomaszewski, RSC Adv., 2022, 12, DOI: 10.1039/D1RA08415A. Issue 50 (14th November 2022) - Kumar, Nitin; Shukla, Alok; Kumar, Nripesh; Choudhary, R. N. P.; Kumar, Ajeet
Abstract : A solid solution of Bi(Co0.40 Ti0.40 Fe0.20 )O3 was synthesized via a simple and cost effective solid-state technique, and various properties were investigated. Phase identification of the samples was performed using powder X-ray diffraction data with POWDMULT software. Abstract : The cobalt and titanium modified BiFeO3 [ i.e., Bi(Co0.40 Ti0.40 Fe0.20 )O3 ; referred to as BCTF80/20] solid solution was synthesized via a simple and cost effective solid-state technique, and numerous sets of studies (structural, elemental, electrical, leakage current, multiferroic and other properties) were carried out and reported. The basic structural symmetry was investigated and phase identification of the prepared samples was carried out by analyzing powder X-ray diffraction data through the widely used "POWDMULT" software. From the XRD pattern [Fig. 2(a) of RSC Adv., 2018, 8, 36939], it is clear that almost all the reflection peaks (including those that appear to be split) have been indexed to a single phase (based on the best agreement between experimental and calculated interplanar distances and minimum standard deviation) system using the above software. The lattice parameters, average crystallite size, cell volume, and micro-strain value are strongly affected by the addition of Co and Ti into the bismuth ferrite. The significant enhancement of various parameter ( i.e., electrical, multiferroic and so on) values of BCTF80/20 ceramics may make them promising candidates for the development of new generation electronic devices.